Clinical Implication of Adherent Perinephric Fat in Robot-Assisted Partial Nephrectomy: Validation With Video Review - Kim, Hwanik; Kim, Myeongju; Byun, Seok-Soo; Hong, Sung Kyu; Lee, Sangchul (Frontiers in Surgery, 2022)
Objective To assess the impact of adherent perinephric fat (APF) on perioperative outcomes of robot-assisted partial nephrectomy (RAPN). Methods A total of 562 Asian patients with kidney tumors received RAPN and their Mayo adhesive probability (MAP) scores were evaluated. APF was determined intraoperatively and confirmed by a second surgical video review and perioperative data were compared according to the MAP score. The associations of APF with clinical factors were examined using logistic regression analyses. Subgroup (classified according to who performed the surgery) analysis was conducted to assess if the perirenal dissection time is significantly correlated with APF. Results A total of 118 consecutive patients were classified into two groups according to APF. Patients in the APF group needed significantly longer perirenal fat dissection time (p < 0.001) and longer hospital stay (p = 0.028). MAP score (Odds ratio [OR]: 2.71, 95% Confidence interval [CI]: 1.56–4.71, p < 0.001), body mass index (OR: 1.24, 95% CI: 1.04–1.47, p = 0.016), and perirenal fat dissection time (OR: 1.11, 95% CI: 1.03–1.19, p = 0.004) were significantly associated with the presence of APF. Perirenal fat dissection time was significantly correlated with APF presence in two of three surgeon subgroups (ß = 8.117, p = 0.023; ß = 7.239, p = 0.011). Conclusions Preoperative MAP score and perirenal fat dissection time were significantly associated with APF during RAPN.